PENGARUH MEDIA SOSIAL TIKTOK TERHADAP PERKEMBANGAN BAHASA GAUL DIKALANGAN REMAJA DESA LUBUK PUA KECAMATAN VII KOTO SUNGAI SARIK - Permata, Okma (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Language is speech sounds that are pronounced through speech organs which function as a means of communication in everyday life. Slang itself is the typical language of a group of teenagers, because the words spoken are changed in such a way that only they understand the intent and purpose. The slang he speaks is also influenced by social media. In general, almost all teenagers have social media on their Android. Android already has several applications for communicating, such as the TikTok application. This research aims to determine the widespread use of slang among teenagers in Lubuk Pua Village, VII Koto Sungai Sarik District. This research uses a qualitative descriptive method. The processing and data collection techniques are carried out through observation, interviews and notes. The subjects in this research were teenagers from Lubuk Pua Village, VII Koto Sungai Sarik District. The results of this research show that the existence of TikTok social media can influence the language of teenagers, the language they acquire is slang. The use of the TikTok application by teenagers is the same as the use of addictive substances, namely they are addicted or dependent. The influence of social media such as TikTok is very large, because the slang that appears can damage the standard vocabulary of the Indonesian language itself, because the vocabulary is shortened and absorption from foreign languages occurs. So, as teenagers who use social media, they must be able to use this slang and not use it often when speaking because it can damage the Indonesian language.Keywords: Social Media, Slang.